Nososticta nicobarica sp. nov. (Odonata: Platycnemididae: Disparoneurinae) from Great Nicobar Island, India - Rajeshkumar, S.; Raghunathan, C.; Chandra, Kailash (Zootaxa, 2017)
The damselfly Nososticta nicobarica sp. nov. (Odonata: Platycnemididae: Disparoneurinae) is described (holotype ♂: ZSI-ANRC-T-4418; 11.ii.2016) from Gandhi Nagar, Great Nicobar Island in the Andaman & Nicobar Islands, India. This is the first record for the genus Nososticta from the Indian sub-continent, and a formal description is given. The new species is described on the basis of male anal appendages, particularly cerci with a deeply bifurcate, acute apex, distinctly curved downward. Paraprocts almost straight with blunt apex slightly curved upward and inner margin with small, roughly rectangular hook. The female is characterised by the anterior lobe of the pronotum, which bears two long, divergent horn-like processes and a short posterior lobe with paired club-shaped processes. Affinities with species of Lesser Sundaic region are discussed.